Tenascin C in the Tumor-Nerve Microenvironment Enhances Perineural Invasion and Correlates With Locoregional Recurrence in Pancreatic Ductal Adenocarcinoma. Issue 3 (March 2020) - Furuhashi, Satoru; Sakaguchi, Takanori; Murakami, Tomohiro; Fukushima, Mayu; Morita, Yoshifumi; Ikegami, Koji; Kikuchi, Hirotoshi; Setou, Mitsutoshi; Takeuchi, Hiroya
Abstract : Objectives: Perineural invasion is common in pancreatic ductal adenocarcinoma (PDAC) and worsens the postoperative prognosis. Tenascin C (TNC), an extracellular matrix glycoprotein, modulates tumor progression. We evaluated the functional roles of TNC, especially in perineural invasion of PDAC. Methods: We examined immunohistochemical TNC expression in 78 resected PDAC specimens. The relationships between TNC expression and clinicopathological features were retrospectively analyzed. Interactions between cancer cells and nerves with TNC supplementation were investigated using an in vitro coculture model with PDAC cell line and mouse dorsal root ganglion (DRG). Results: Tenascin C expression was predominant in perineural sites at the invasive tumor front. High perineural TNC expression in 30 patients (38%) was associated with perineural invasion, pathological T stage ≥3, and postoperative locoregional recurrence. High TNC expression was independently associated with postoperative, poor recurrence-free survival by multivariate analysis. In the in vitro coculture model, a TNC-rich matrix enhanced both PDAC cell colony extensions toward nerves and DRG axonal outgrowth toward cancer cell colonies, whereas TNC did not affect axonal outgrowth or cancer cell proliferation in separately cultured DRG and PDAC cells. Conclusions: Strong perineural TNC expression indicated poor prognosis with locoregional recurrence. The neurotropism of TNC-induced PDAC suggests that TNC is a potential PDAC therapeutic target. Abstract : Supplemental digital content is available in the text.